2016
DOI: 10.15376/biores.11.3.5974-5986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glass Wool and Stone Wool Additives on Some Mechanical Properties of Wood Composites

Abstract: Mechanical properties of wood composites made from multiple wood species (50% Crimean pine, 30% Eastern Black Sea oak, 15% quaking aspen, and 5% wood machining residues) were evaluated using various amount of glass wool (GW) and stone wool (SW) additives. A total of 70 experimental panels were produced with a target density of 640 kg/m 3 . The bending strength, modulus of elasticity, tensile strength parallel to the surface of boards, tensile strength perpendicular to the surface of boards (internal bond), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Özdemir (2019) reported that the use of dolomitic sepiolite and perlite minerals in different proportions in the production of MDF negatively affected the physical and mechanical properties of the board. The use of glass fiber and stone wool in particleboard production, depending on the type of adhesive and additive ratio, reduced the mechanical properties of the boards by 75% from 39% (Ülker and Burdurlu 2016).…”
Section: Mechanical and Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Özdemir (2019) reported that the use of dolomitic sepiolite and perlite minerals in different proportions in the production of MDF negatively affected the physical and mechanical properties of the board. The use of glass fiber and stone wool in particleboard production, depending on the type of adhesive and additive ratio, reduced the mechanical properties of the boards by 75% from 39% (Ülker and Burdurlu 2016).…”
Section: Mechanical and Physical Propertiesmentioning
confidence: 99%
“…They reported that because the mechanical properties of these materials were at a good level, they could be used in wood-plastic composites of the type widely used in flooring applications. As a result of examining the mechanical properties of particleboards produced using glass wool and stone wool, Ülker and Burdurlu (2016) reported that the glass wool and stone wool reduced the bending strength and modulus of elasticity of the board 49%, shear strength by 8%, screw tensile strength by 3%, and tensile strength by 6%. Mamiński et al (2011) investigated the thickness swelling and mechanical and thermal properties of particleboards produced by adding mineral wool at the rates of 10, 20, and 30% using UF resin as a binder.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of wood, such as strength, hardness, and abrasion, can be improved by densification due to the compression perpendicular to grain under high temperature and pressure (Haller and Wehsener, 2004;Kollmann et al, 1975;Seborg et al, 1956;Ülker and Burdurlu, 2016). Thus, it is possible to use the wood of fast-growing species with low density and low mechanical properties as structural material instead of high-value wood (Kutnar and Sernek, 2007).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…Thus, it is possible to use the wood of fast-growing species with low density and low mechanical properties as structural material instead of high-value wood (Kutnar and Sernek, 2007). Wood surface roughness is also reduced by densification, which provides lower press time, press pressure, press temperature, and less glue, especially in the production of laminated materials such as plywood and laminated veneer lumber (LVL) ( In the literature, there are many studies on the production of laminated materials such as plywood and LVL from pre-densified veneer (Bekhta and Ülker and Burdurlu, 2016). However, the densification of veneer as a separate step before lamination increases production time and cost.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…Wood and wood-based materials are important components of furniture design and furniture construction design. The advance knowledge of the behavior of such materials regarding physical and mechanical forces applied to furniture provides technical, aesthetic, and economic benefits to the designer, manufacturer, and eventually users (Eckelman 1979, Kasal et al 2016, Imirzi et al 2016, Cinar et al 2019, Ulker and Burdurlu 2016.…”
Section: Introductionmentioning
confidence: 99%